What is the value of 64 ÷ 2 ∙ 16.

Answers

Answer 1
Answer: 64 : 2 · 16 = 32 · 16 = 512
Answer 2
Answer: 64/2 is 32, and 32 times 16 is 512, which is your answer

Related Questions

Which type of lines pass through points (2, 5), (8, 7) and (-3, 1), (-2, -2) on a grid?PERP PARRELL OR NONE?
Multiply 4/9 x 1 & 4/5 x 2/5 A. 1 & 32/45 B. 7/16 C. 8/25 D. 1 & 10/19
Solve photo question. Mathematics again.
A family is having a pool built in their backyard. If their yard is rectangular and measures 7x by 6x and the pool is circular with a radius of 2x how much of the yard will be left over after the pool is built?a. 38x2 b. 42x2 – 4x2 c. 42x2 – 2x2 d. 38x2
Simplify 4 to the seventh power over 5 squared all raised to the third power.

Sal and two of his friends rent an apartment together. Their total cost to move in included first months rent, last months rent and a security deposit of $1,200. If Sal paid a total of $1,000 to move in, how much is his share of the rent each month?.

Answers

according to the problem the payment Sal did correspond to
(2 rent + 1200)/3 = 1000
2 rent + 1200 = 3000
2 rent = 1800
rent = 900
this means that 
rent = $900

Answer:

according to the problem the payment Sal did correspond to

(2 rent + 1200)/3 = 1000

2 rent + 1200 = 3000

2 rent = 1800

rent = 900

this means that

rent = $900

Step-by-step explanation:

Find the least common multiple of 7 3 2

Answers

The answer should be 42

Six years after a tree was planted, its height was 7 feet. Nine years after it was planted, its height was 16feet. Which of the following equations gives the heighty, in feet, of the tree after x years if the tree grows at
a constant rate? Check all of the boxes that apply.
y - 6 =3(x - 10)
y-16 = 3(x-9)
y = 3x - 11
y=-3x - 23

Answers

I'm not good in this but.....

x = years

9x-6x = 16-7

3x = 9

x = 3

That means the tree will grow three feet per year.

Find the sum of the given polynomials.ax + by + c, 2ax - 3by + c, and by - c

3ax - by + c
3a + x - bc
3ax + by - cd
bx - 3bc + a

Answers

  ax +  by + c
2ax - 3by + c
            by - c   
3ax - by + c   First Option.

You must align like terms before adding them. This is to ensure that there will be no confusion in getting the sum of the given polynomials.
If you would like to find the sum of the given polynomials, you can do this using the following steps:

ax + by + c + 2ax - 3by + c + by - c = ax + 2ax + by - 3by + by + c + c - c = 3ax - by + c

The correct result would be 3ax - by + c.

Which of the following are true statements about the expression 5 + (-5) 1. the expression equals 0.
2. The expression equals 10.
3. The expression describes the number that is 5 to the left of 5 on the number line.
4. The expression describes the number that is 5 to the right of 5 on the number line.

Answers

Answer:

\huge\boxed{\sf The \ expression\ equals \ zero}

Step-by-step explanation:

=> 5 + (-5)    [ + (-) = - ]

=> 5 - 5

=> Zero

Final answer:

The expression 5 + (-5) equals 0 and describes the number that is 5 to the left of 5 on the number line.

Explanation:

The true statements about the expression 5 + (-5) are:

  1. The expression equals 0.
  2. The expression describes the number that is 5 to the left of 5 on the number line.

When we add a positive number and a negative number with equal magnitudes, the result is always 0. In this case, 5 + (-5) equals 0. Alternatively, we can interpret the expression as starting from 5 and moving 5 units to the left (in the negative direction), which also leads to 0 on the number line.

Learn more about Addition of positive and negative numbers here:

brainly.com/question/34274134

#SPJ2

What is the greatest common factor of 60x4y7, 45x5y5, and 75x3y?

Answers

factor and group common ones
60=2*2*3*5*x*x*x*x*y*y*y*y*y*y*y
45x^5^5=3*3*5*x*x*x*x*x*y*y*y*y*y
75x^3y=3*5*5*x*x*x*y

the commmon gropu to all is 3*5*x*x*x*y=15x^3y